Strategy Development for Professional School Directors under Kamphaengphet Primary Educational Service Area Office 1 and Office 2 - Pongkanta, Sukittaya; Wongnaya, Somchai; Boonphithak, Sunee (Humanities and Social Sciences Journal of Pibulsongkram Rajabhat University, 2018)
The objectives of this research were 1) to study the characteristics of professional school directors, by analyzing the documents and a questionnaire; data were collected from the experts, school directors, teachers, 2) to study the states, the problems and the factors related to professional school directors, using the questionnaire and group discussion; data were collected from school directors, teachers, 3) to develop strategies of professional school directors, 2 workshops and expert seminars; data were collected from educational administrators, school directors, teachers, and 4) to assess the strategies of professional school directors, using the strategic assessment; data were collected from educational administrators, school directors, and professionals and analyzed by using frequency, mean, standard deviation and content analysis The research showed that 1) the characteristics of professional school directors in every aspect overall were at a high level and when considering by items it was found that they had moral and ethics the most; whereas they had professional in academic characteristics the least. 2) The state, problems and factors were at a high level in all aspects. In terms of development, it was found that the school directors developed themselves from their working units the most. The development problem found that the school directors lacked the development plan and monitoring and evaluation. The strength on development factors found that the school directors performed their jobs concretely, were eager to learn the development. The weakness found that the school directors had an unclear plan, without system, undiversified formats, lack self-analysis, discontinuous follow up, inadequate budget. In terms of opportunity, it was found that policy: the society focused on the importance of development support, speedy technology which supported the utility. In terms of threats, the changing social and economic threats resulted to the budget allocation for discontinuous project/activity. 3) The strategic development for professional school directors comprised Vision, Mission, Strategic Objectives, Strategy Issues, Strategy, Indicators and Measures. The strategy developed 7 strategies for the organization as follows: 1) Self-development plan for professional school directors should be well-managed. 2) School directors’ abilities were developed for professional levels. 3) School directors should be supported to use research and innovations for school development continuously. 4) School directors should be promoted in their abilities of using English and information technology. 5) Learning informational data should be improved to be modern. 6) Development network should be supported. 7) The process of evaluation should be developed for efficient management. There were 4 strategies for self-development as follows: 1) The plan for self-development should be well-managed. 2) The characteristics of professional school directors should be supported to meet the roles of school directors in the 21st Century. 3) School directors should improve themselves with the development plan. 4) School directors should assess themselves and also improve themselves with the evaluation results. The results of the strategic evaluation were consistent, feasible, possible and useful.